An Extended Virtual Force-Based Approach to Distributed Self-Deployment in Mobile Sensor Networks - Jun Li; Baihai Zhang; Lingguo Cui; Senchun Chai (International Journal of Distributed Sensor Networks)
Virtual physics based approach is one of the major solutions for self-deployment in mobile sensor networks with stochastic distribution of nodes. To overcome the connectivity maintenance and nodes stacking problems in the traditional virtual force algorithm (VFA), an extended virtual force-based approach is investigated to achieve the ideal deployment. In low- R c VFA, the orientation force is proposed to guarantee the continuous connectivity. While in high- R c VFA, a judgment of distance force between node and its faraway nodes is considered for preventing node stacking from nonplanar connectivity. Simulation results show that self-deployment by the proposed extended virtual force approach can effectively reach the ideal deployment in the mobile sensor networks with different ratio of communication range to sensing range. Furthermore, it gets better performance in coverage rate, distance uniformity, and connectivity uniformity than prior VFA.